Parental Property Equal Right Policy of Nepal: A Focus Group Discussion of Students of Law Faculty of Kathmandu - Acharya, Chiranjivi (Research Nepal Journal of Development Studies, 2021)
It is general fact that the parental property equal rights are the rights of son and daughter upon parents’ properties, rights to ownership into the parents’ properties, rights to get properties earned by parents, rights of properties acquired in accordance with the inheritance, ownership rights to house, money, land and other properties earned by parents and forefather. The property right is a national issue and it is also related to the economy, which is one of the important factors for the development of the country. Unless it would not identify the property-related issue because its effort to change in society will be meaningless. The main objective of the study is to analyze the Parental property equal rights policy of Nepal. To find the objective this article is prepared based on primary information direct group discussion with Law students of different Law Colleges of Kathmandu Valley. Specifically, it is to find quality information regarding the existing policy of parental property equal rights system in Nepal. The researcher has not used the information besides as mentioned objectives. The researcher has applied the analytical research methods and inductive approach to make the meaning full of the information. The obtained information is explained in extended forms without disregards what the participants said. As research results that there have been found lots of changes (19 important issues discussed below) in women’s lifestyle after initiating the parental property equal right system in Nepal. The policy program is highly appropriate and welfare for equal existence of women in the society